Competencias investigativas: Una nueva forma de gerenciar la educación media general: Research competencies: a new approach to managing general secondary education - Puche Villalobos, Deinny (Encuentro Educacional, 2024)
There is an urgent need to adapt to contemporary demands in the educational field. In a context where knowledge is constantly transforming and updating, it is essential that secondary education institutions develop research competencies that allow them to manage and oversee institutional guidelines effectively. The objective was to determine the importance of research competencies in fostering a new way of managing general secondary education. Thus, it was based on the theoretical postulates of Rondón (2024), Puche (2024), Morales (2023), Acosta y Barreto-Rodríguez (2023), Hernández (2020), among others. Methodologically, it followed the pragmatic paradigm, with a mixed approach combining a questionnaire administered to 42 school administrators and interviews conducted with 8 of them. The quantitative results revealed that a significant majority of administrators (66.6%) perceive their ability to evaluate problems in the educational environment as moderate. Regarding data interpretation, most (66.0%) perceive this skill as moderate. In terms of decision-making, 59.6% of administrators rate this competency as deficient. From the qualitative perspective, the findings show that deficiencies in problem evaluation are mainly due to a lack of training in research techniques and critical analysis. It is concluded that administrators have developed research competencies at a moderate level.